Ironies of Christian Presence in Southern Africa - Masondo, Sibusiso (Journal for the Study of Religion, 2018)
Christianity was meant to be one of the most potent weapons in the armory of European Imperialism. John Philip characterized mission stations as the cheapest and the best military posts any wise government can employ to defend its frontiers against the predatory incursions of savage tribes (Villa-Vicencio 1988:44). Christianity was meant to colonize the conscience and consciousness of the colonized in ways that would make them lose their indigenousness. It was meant to ‘make’ or ‘create’ the colonized in the image of the colonizer. The irony of this situation is that, among other things, it created conditions for the desire among the colonized to be free; it contributed to the emergence of African Nationalism through notions like ‘brotherhood’ and ‘oneness in Christ’. It became a serious problem for the Christianized and educated natives to find themselves excluded from the Christian family on the basis of their ethnicity. David Chidester’s work on the history of religion in Southern Africa provides a very useful background for exploring the ironies of Christian presence in Southern Africa. Lamin Sanneh’s observation about the role played by indigenous religions to enable both Islam and Christianity to take root is invoked in this context. Christianity became part of the complex that laid the foundations for African nationalism and the pan-Africanist ideology. It provided a platform in mission stations and mission schools for the forging of a unified African identity. Education, given to Africans to become ‘civilized’ and alienated from their African compatriots, instead, helped in creating a consciousness for liberation among the oppressed Africans.